Efforts of the Sabhara Patrol Unit in Preventing Motor Vehicle Thefts in the Cimahi Police Jurisdiction Area - Mirwan, Muhammad (Police Studies Review, 2024)
Modernization and urbanization have an impact on changes in the situation and conditions of security and vulnerability in the Cimahi Regional Police Legal Area. These changes cause various kinds of problems, one of which is a criminal act of motor vehicle theft. The results of the data obtained stated that the problem was caused by the economic level of the Cimahi community which was still low, therefore it was necessary to take preventive measures by the patrol unit in the form of patrol activities. This study aims to describe the development of motor vehicle theft in the jurisdiction of the Cimahi Police Station, describe the factors affecting the Sabhara Unit Patrol Unit in preventing motor vehicle theft, and describe the efforts of the Patrol Unit in preventing motor vehicle theft in the Cimahi Regional Police jurisdiction. The research method used is a qualitative descriptive method which is taken through interviews, observations, and documentation, and data verification using source triangulation and time triangulation. The findings show that the crime of motor vehicle theft has increased every year from 2018 to 2019 and is the highest crime among other cases that occur in the Cimahi Police Precinct. The results of the SWOT analysis conducted by the author indicate that there are 2 (two) factors that influence the efforts of the Patrol Unit in preventing criminal acts of motor vehicle theft, namely internal and external factors. Internal factors consist of the Quantity of Patrol Personnel, and the Need for Fuels, while the External Factors consist of the population of the Cimahi Community and the Cimahi Community Kamtibmas Awareness Level. The Patrol Unit has made a Preventive effort in the form of a Dialogical Patrol which is a breakthrough of the Sabahara Unit in carrying out patrols. However, after being analyzed using POAC Management Theory, the Cimahi Police Patrol Unit's preventive efforts are still not good, so the author recommends the Cimahi Police Patrol Unit to increase the intensity of patrol implementation, and make effective dialogical patrols with the community.